(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The ability to speak fluently and confidently is a crucial aspect of language learning. However, many language learners struggle with developing their speaking skills due to a lack of practice and confidence. The shadowing method is a highly effective technique that can help students improve their speaking abilities in a fun and engaging way. In this article, we will explore the shadowing method in more detail, including how it works, its benefits, and practical steps for implementing it in the language classroom. Additionally, we will provide tips for successful shadowing practice and strategies for assessing student progress through this method. By the end of this article, language teachers will be equipped with the knowledge and skills to effectively incorporate the shadowing method into their teaching practice and help students become more proficient speakers.